2003
DOI: 10.3102/00028312040001043
|View full text |Cite
|
Sign up to set email alerts
|

What Is Tracking? Cultural Expectations in the United States, Germany, and Japan

Abstract: On the basis of the TIMSS Case Study Project data collected in the United States, Japan, and Germany in 1994-1995, this article examines the phenomenon of tracking as part of curricular differentiation and student placement practices in public K-12 school systems. The authors document clear national differences in differentiation and placement measures and summarize the history of conflict over those measures. Analysis of respondent perceptions and beliefs about differentiation and placement (what people thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 72 publications
0
113
0
6
Order By: Relevance
“…This is surprising because many educational systems implement at least some kind of tracking, particularly in secondary education (Chmielewski, Dumont, & Trautwein, 2013;LeTendre, Hofer, & Shimizu, 2003).…”
Section: Generalizability Across School Tracksmentioning
confidence: 99%
“…This is surprising because many educational systems implement at least some kind of tracking, particularly in secondary education (Chmielewski, Dumont, & Trautwein, 2013;LeTendre, Hofer, & Shimizu, 2003).…”
Section: Generalizability Across School Tracksmentioning
confidence: 99%
“…If so, the message does not seem to have reached parents whose children were in regular/low classes. Past and recent research suggests that many parents of students in lowerlevel classes have less education and less knowledge of school systems than parents of children in higher-level classes, as well as less access to informal networks that help them obtain information about school placements, including how to override normal placement channels (Apple 2001;Auerbach 2002;LeTendre et al 2003;Rosenbaum 1976). Parents who do not speak English, who do not feel comfortable in schools, whose skin color differs from those in charge, and who take class labels at face value have more limited chances of successfully advocating for their children (Auerbach;Fine et al 2005).…”
Section: Differences In Instruction and Classroom Environmentmentioning
confidence: 97%
“…Judging from research and reviews written since that time, many educators and researchers believe the lessons learned from research about the damaging effects of ability grouping have been applied in educational practice and that the differential instruction of current times bears no resemblance to the tracking Urban Rev (2010) 42:271-295 275 and ability of the past (Barr 1995;LeTendre et al 2003;Lucas 1999;Rogers 2004Oakes 2005. However LeTendre et al (2003) suggested that the practice of comparing, sorting, and classifying students has not vanished in the U.S. but has merely become a back-burner issue, and a recent resurgence of research and academic debate suggests that ability grouping is again (or still) thriving (Blanchett 2006;Chorzempa and Graham 2006;Orfield and Lee 2004;Watanabe 2006;Yonezawa and Jones 2006).…”
Section: Academic Social and Emotional Consequences Of Ability Groumentioning
confidence: 98%
“…Esta aproximación está dominada por la exploración de los efectos institucionales. Especialmente fecundo es el debate sobre la influencia de las formas de diferenciación escolar y, más concretamente, de dos de las cinco distinguidas en la clasificación de LeTendre et al (2003): los itinerarios educativos o tracking, y el agrupamiento por capacidades (Pfeffer, 2015). Las investigaciones concluyen que la diferenciación obstaculiza tanto la igualdad de oportunidades como la calidad educativa, y que, consecuentemente, no hay evidencia de que dé lugar a un trade-off entre ambas (Pfeffer, 2015;Van de Werfhorst y Mijs, 2010).…”
Section: La Tensión "Calidad-equidad"unclassified